2014
DOI: 10.1186/1746-6148-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens strains from bovine enterotoxemia cases are not superior in in vitroproduction of alpha toxin, perfringolysin O and proteolytic enzymes

Abstract: BackgroundBovine enterotoxemia is a major cause of mortality in veal calves. Predominantly veal calves of beef cattle breeds are affected and losses due to enterotoxemia may account for up to 20% of total mortality. Clostridium perfringens type A is considered to be the causative agent. Recently, alpha toxin and perfringolysin O have been proposed to play an essential role in the development of disease. However, other potential virulence factors also may play a role in the pathogenesis of bovine enterotoxemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Enteritis caused by C perfringens type A is observed in calves, lambs, and kid goats. 1,3,10,25,30,47,50,64,65 Enteritis is generally acute and develops over a period of hours. Appetite is significantly decreased.…”
Section: Type Amentioning
confidence: 99%
“…Enteritis caused by C perfringens type A is observed in calves, lambs, and kid goats. 1,3,10,25,30,47,50,64,65 Enteritis is generally acute and develops over a period of hours. Appetite is significantly decreased.…”
Section: Type Amentioning
confidence: 99%
“…Furthermore, pre-treatment of sensitive cells with NanI sialidase enhanced the subsequent binding and cytotoxic effects of epsilon toxin, suggesting that the large sialidases of C. perfringens can act in synergy with this toxin during type D enterotoxaemia [ 106 ]. However, no difference in in vitro mucin-degrading activities between C. perfringens strains originating either from bovine necro-haemorrhagic enteritis cases, from healthy cattle isolates or from other animal species could be demonstrated [ 108 ]. This, however, does not exclude a possible role of mucin-degrading enzymes in intestinal pathogenesis as the production of virulence factors in vitro does not necessarily reflect the in vivo situation, where contact with host tissue might alter the C. perfringens toxin production.…”
Section: Virulence Factors Involved In Diseasementioning
confidence: 99%
“…The same inhibition was not observed with the use of MAb 318F11B7. In a recent study carried out in bovine enterotoxemia strains, was shown an activity of alpha toxin below the detection limit of 15.6 10 − 3 U/ml and that were not significantly different from levels produced by strains isolated from healthy calves [29]. We detected an increased CPA activity only in the culture supernatants of three C. perfringens strains originating from enterotoxoemia cases and this in accordance with hypothesis that, a hither to unknown, C. perfringens virulence factor might be involved in the pathogenesis of calf enterotoxemia.…”
Section: Discussionmentioning
confidence: 89%
“…Plates were incubated at 37°C for 24 h and the diameters of the zones of opacity were measured using a calibre. The lecithinase activity (U/ml) was quantified using a standard curve, in which the log of concentration of the PLC standard was plotted against the radial diffusion diameter of turbidity [29].…”
Section: Cpa Toxin Biological Activity With Eydt Assaymentioning
confidence: 99%